PERANCANGAN SISTEM PENGAMBILAN OBAT BERBASIS WEB PADA RSU CAHAYA MEDIKA - Satrio Singgih; Handini Widyastuti; Bambang Junadi; Yuni Fitriani; Sri Utami; Renditya Akbar (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
The Medication pickup process at RSU Cahaya Medika is still manual, causing delays, queues, and data errors. This study aims to implement a web-based information system to improve pharmacy service efficiency and accuracy. The system was developed using the waterfall model with PHP, MySQL, and Framework. It helps manage prescriptions, medication status, and reports in an integrated way. The result show that the system speeds up services, reduces errors, and provides clear information to patients. It is expected to enhance the performance of the hospital pharmacy.